Downregulation of ATP1A1 Expression by Panax notoginseng (Burk.) F.H. Chen Saponins: A Potential Mechanism of Antitumor Effects in HepG2 Cells and In Vivo - Feng, Xiao-Yi; Zhao, Wei; Yao, Zheng; Wei, Ning-Yi; Shi, An-Hua; Chen, Wen-Hui (Frontiers in Pharmacology, 2021)
Na+/K+-ATPase α1 subunit (ATP1A1) as a potential target for hepatic carcinoma (HCC) treatment, which plays key roles in Na+-K+ exchanging, metabolism, signal transduction, etc. Our study aims are to explore the potential effects of Panax notoginseng saponins (PNS) on the regulation of ATP1A1, and the possible mechanisms of anticancer. The effects of PNS on HepG2 cell viability, migration, and apoptosis assays were examined in vitro, respectively. Fluorescence, western blot, and RT-PCR analyses were also used to examine the genes and protein expression associated with ATP1A1 signal transduction. Further analysis was assessed by Na+/K+-ATPase inhibitor (Digitonin) in vitro. We found that ATP1A1 expression was markedly higher in HepG2 cells than in LO2 cells, and PNS exhibited a dose-dependent effect on the expression of ATP1A expression. PNS treatment led to down-regulate the phosphate of AKT, ERK proteins, and the expression of ATP1A1 protein in HepG2 cells. Digitonin could inhibit the activity of Na+/K+-ATPase，but did not affect the expression of ATP1A1. Digitonin could affect the effects of PNS on the regulation of ATP1A1/AKT/ERK signaling pathways, and increase the anti-tumor effect of PNS by changing the permeability of the cell membrane to promote cell death happening. Taken together, PNS affected inhibitory effects on HepG2 cells via ATP1A1 signal transduction. Our findings will aid a data basis for the clinical use of PNS.